The politics of cyberconflict: ethnoreligious conflicts in computer mediated environments - Karatzogianni, Athina (2005)
This thesis argues that it is important to distinguish between two different phenomena in cyberpolitical spaces: First of all, between ethnic or religious groups fighting over in cyberspace, as they do in real life (Ethnoreligious cyberconflict) and second, between a social movement and its antagonistic institution (Sociopolitical cyberconflict). These different kinds of cyberconflict can be explained in the context of international conflict analysis for ethnoreligious cyberconflict and social movement theory for sociopolitical cyberconflict, while keeping in mind that this takes place in a media environment by using media theory. By combining elements of these approaches and justifying the link to cyberconflict, it is possible to use them as a theoretical light to look at the environment of Cyberconflict (CC) and analysis of incidents of CC. Consequently, this work looks at the leading groups using the internet either as weapon or a resource against governments, while also looking at networks, international organisations and new social movements. Searching for a satisfactory theoretical framework, I propose the following parameters to be looked at while analysing cyberconflicts: